2017
DOI: 10.1002/2017gl074858
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of IMF Clock Angle on Dayside Flux Transfer Events at Mercury

Abstract: Analysis of MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER) data has shown for the first time that the orientation of the interplanetary magnetic field (IMF) in the magnetosheath of Mercury plays a crucial role in the formation of flux transfer events (FTEs) at the dayside magnetopause. During the first 4 Hermean years of MESSENGER's orbit around Mercury, we have identified 805 FTEs using magnetometer data. Under conditions of near-southward IMF, at least one FTE was detected on nearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 55 publications
2
21
0
Order By: Relevance
“…Although we have regarded the solid line as a “sensible upper limit” based on the extreme value of B N , the effect of using an upper limit value for r (1600 km; based on the upper end of the duration range reported by Imber et al, ) is indicated by the dotted line. Changing this assumption increases the flux content by a factor of 3.2; a flux content of 1 MWb is obtained for an X‐line length of ∼4.5 hr of MLT, comparable to the length we might infer from the FTE statistics reported by Leyser et al (), and values of Φ total equivalent to the mean and extreme values of Φ rope reported by Imber et al () are obtained for X‐line lengths of ∼0.25 and 1 hr of MLT, respectively.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Although we have regarded the solid line as a “sensible upper limit” based on the extreme value of B N , the effect of using an upper limit value for r (1600 km; based on the upper end of the duration range reported by Imber et al, ) is indicated by the dotted line. Changing this assumption increases the flux content by a factor of 3.2; a flux content of 1 MWb is obtained for an X‐line length of ∼4.5 hr of MLT, comparable to the length we might infer from the FTE statistics reported by Leyser et al (), and values of Φ total equivalent to the mean and extreme values of Φ rope reported by Imber et al () are obtained for X‐line lengths of ∼0.25 and 1 hr of MLT, respectively.…”
Section: Discussionsupporting
confidence: 77%
“…In terms of inferences from MESSENGER observations, we can draw conflicting conclusions. Leyser et al () reported that, despite fairly uniform coverage of magnetopause crossings through dayside magnetic local times, most FTEs were observed within 3 hr of MLT from noon, which suggests that a maximum typical X‐line length may be <6 hr of MLT. On the other hand, DiBraccio et al () surveyed magnetopause crossings for rotational discontinuities and found the magnetopause was open on crossings between 8 and 16 hr local time.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The coupling of the interplanetary magnetic field and the solar wind with the planetary magnetosphere is much stronger than previously believed, owing to the almost- continuous dayside magnetic reconnection (e.g. , as proved by the frequent observations of flux transfer events (FTE) Leyser et al 2017) (Fig. 1 upper panels).…”
mentioning
confidence: 85%